العلاقات السياسية والاجتماعية بين المماليك 648-923هـ/ 1250-1517 ( الخشداشية انموذجا) (Journal of the College of Basic Education, 2023)
The Mamluk style of life differed from that of other peoples , as their families were not based on one-blood relations , but rather on relationships Slavery , slavery , and the interconnectedness of their lives and their strict military upbringing left the counter This was owned The little and a father , especially since he lives as a stranger in a country that is not his own Forced separation from their families and homelands , they found alternative relationships , and created relationships similar to those of a real family but with different names , since the structure of Mamluk society was based on what could be called “ the family “ Mamluk . Like the professor , who is like a father to the salve , and the agha , who is the big brother and the one who is like a brother in addition to other bonds , the most important of which was the bond of ( al-Khashashiya ) or (collegiality) or (brotherhood) , This bond affected the strength and weakness of the sultans and was a double – edged sword , as the more Khashashaya Amir among the princes , the higher his status , and vice versa , the less Khashdashiya one of the princes became . His weakness and the reason for his exposure to many conspiracies and temptations , so the Mamluk sultans were keen to strengthen and encourage this relationship between their Mamluk is the source of their strength and their survival in power as long as possible little .